2017
DOI: 10.26417/ejser.v11i2.p340-349
|View full text |Cite
|
Sign up to set email alerts
|

Can Mobile Learning Be An Opportunity for Undergraduate Teacher Education?

Abstract: The purpose of research is to determine the usability of mobile learning in undergraduate teacher education. In the first part of the study, researches on mobile learning opportunities in undergraduate teacher education and teacher education are examined. In the second part of the study, infrastructure and readiness for mobile learning of prospective teachers are examined in terms of some variables. The research is designed in survey model. The sample of the research is composed of 454 prospective teachers who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Both factors scored the highest overall mean of the scale. This finding is consistent with that of Baş and Sarıgöz (2018) and Eroğlu et al (2017) who also found selfefficacy as the highest overall mean of the scale. A possible explanation for this might be that the participants of this study were certain in their ability to utilize a smartphone for their English language learning since they have many experiences with the smartphone.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Both factors scored the highest overall mean of the scale. This finding is consistent with that of Baş and Sarıgöz (2018) and Eroğlu et al (2017) who also found selfefficacy as the highest overall mean of the scale. A possible explanation for this might be that the participants of this study were certain in their ability to utilize a smartphone for their English language learning since they have many experiences with the smartphone.…”
Section: Discussionsupporting
confidence: 92%
“…Many recent studies (e.g. Ata & Cevik, 2019;Baş & Sarıgöz, 2018;Eroğlu et al, 2017;Tezer & Beyoğlu, 2018) have used this scale to investigate students m-learning readiness.…”
Section: Introductionmentioning
confidence: 99%
“…In the research, it was determined that male and female pre-service teachers' readiness levels did not differ significantly. Parallel to this result, the results of the Baş and Sarıgöz (2018), and Eroğlu et al (2017)'s studies showed that there were no significance difference pre-service teachers' level of mobile learning readiness in terms of gender. Another results obtained from this research was that there was no statistically significant difference in the level of readiness of pre-service teachers in different grade levels.…”
Section: Discussionmentioning
confidence: 68%
“…Considering that the scale applied in this research is 7-Likert type, it could be said that the readiness levels of the pre-service mathematics teachers were partially high. Similarly, in their research Eroğlu et al (2017) concluded that pre-service teachers mobile technology readiness was partially high. In the research, it was determined that male and female pre-service teachers' readiness levels did not differ significantly.…”
Section: Discussionmentioning
confidence: 91%